Na+ deposition in the fibrotic skin of systemic sclerosis patients detected by 23Na-magnetic resonance imaging. (19th December 2016) - Kopp, Christoph; Beyer, Christian; Linz, Peter; Dahlmann, Anke; Hammon, Matthias; Jantsch, Jonathan; Neubert, Patrick; Rosenhauer, Daniela; Müller, Dominik N.; Cavallaro, Alexander; Eckardt, Kai-Uwe; Schett, Georg; et al.
Abstract: Objective. Skin fibrosis is the predominant feature of SSc and arises from excessive extracellular matrix deposition. Glycosaminoglycans are macromolecules of the extracellular matrix, which facilitate Na + accumulation in the skin. We used 23 Na-MRI to quantify Na + in skin. We hypothesized that skin Na + might accumulate in SSc and might be a biomarker for skin fibrosis. Methods. In this observational case–control study, skin Na + was determined by 23 Na-MRI using a Na + volume coil in 12 patients with diffuse cutaneous SSc and in 21 control subjects. We assessed skin fibrosis by the modified Rodnan skin score prior to 23 Na-MRI and on follow-up 12 months later. Results. 23 Na-MRI demonstrated increased Na + in the fibrotic skin of SSc patients compared with skin from controls [mean (s .d .): 27.2 (5.6) vs 21.4 (5.3) mmol/l, P < 0.01]. Na + content was higher in fibrotic than in non-fibrotic SSc skin [26.2 (4.8) vs 19.2 (3.4) mmol/l, P < 0.01]. Furthermore, skin Na + amount was correlated with changes in follow-up modified Rodnan skin score (R 2 = 0.68). Conclusions. 23 Na-MRI detected increased Na + in the fibrotic SSc skin; high Na + content was associated with progressive skin disease. Our findings provide the first evidence that 23 Na-MRI might be a promising tool to assess skin Na + and thereby predict progression of skin fibrosis in SSc.